2018
DOI: 10.1039/c8ra03799j
|View full text |Cite
|
Sign up to set email alerts
|

C–H activation-annulation on the N-heterocyclic carbene platform

Abstract: Ring-fused cationic N-heterocycles are an important class of organic compounds recognized to be of significant interest in diverse research areas including bioactivity, materials chemistry, supramolecular chemistry, etc. Toward the synthesis of such molecules, recently unique chemistry has been explored utilizing a novel conjugative action of NHC ligands as a functionalizable directing group in rhodium(III)catalyzed aromatic/heteroaromatic/non-aromatic C-H activation and subsequent annulation of various imidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…Among these catalytic conversions, annulation is one of the important reactions which produces ring fused heterocyclic cationic compounds (via single step NHC assisted CÀ H activation) having potential applications in medicinal and pharmaceutical research. Although the Rh based catalytic systems are now well developed in such chemistry and has been covered in a recent review, [44] the related Ru-NHC based systems are rather unexplored. In this Scheme 30.…”
Section: Annulationsmentioning
confidence: 99%
“…Among these catalytic conversions, annulation is one of the important reactions which produces ring fused heterocyclic cationic compounds (via single step NHC assisted CÀ H activation) having potential applications in medicinal and pharmaceutical research. Although the Rh based catalytic systems are now well developed in such chemistry and has been covered in a recent review, [44] the related Ru-NHC based systems are rather unexplored. In this Scheme 30.…”
Section: Annulationsmentioning
confidence: 99%
“…Under the optimized conditions (Scheme 4), authors investigated the substrate scope, firstly, in regard of alkynes and found that aryl substituted terminal alkynes bearing either electron-withdrawing or -donating groups on various positions of the aromatic ring afforded products in high yields (38)(39)(40)(41)(42). Moreover, terminal alkynes with aromatic substituents like naphthyl, pyrene, and heterocycles led to high yields (43)(44)(45)(46), while terminal aliphatic substituted alkynes resulted in low to high yields (47)(48)(49)(50)(51). There were only a few examples for internal alkynes with yields being low to moderate (52,53).…”
Section: Annulations Via C(sp 2 )-H Bond Activationmentioning
confidence: 99%
“…Motivated by the above-mentioned needs, researchers have employed the use of functional groups that significantly affect C-H activation reactions. Directing groups (DG) represent an ingenious way to orchestrate and manipulate atoms towards the synthesis of important classes of organic compounds, such as pyrroles, indoles, quinolines, indolinones, and related heterocycles [44][45][46][47][48]. Transition metals can temporarily coordinate to these specific sites on the starting materials, thus leading to the formation of key intermediates that would not form otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…The sample is kept in the oxygen‐free glove box environment for several days at room temperature to evaporate out excess solvent. As 2 S 3 dissolved in alkyl amines can be described as a nanocolloidal solution consisting of flat clusters that internally retain the structure of the layer‐like starting material but capped by ionic pairs of sulfide dangling bonds and alkyl ammonium molecules 31. Without annealing, those solvent‐related atomic defect states suppress light emission from As 2 S 3 14…”
Section: Localized Photon and Heat Distribution In The Hybrid Metasurmentioning
confidence: 99%